My first Bob books. Alphabet - Kertell, Lynn Maslen; Hendra, Sue; Maslen, John R. (New York : Scholastic, 2008)
Presents familiar animal friends for every letter of the alphabet, challenge kids to find objects with featured sound, and offers parents teaching tips and activities to support kids' growth and build confidence.
bk. 1. The AB book -- bk. 2. The CD book -- bk. 3. The EF book -- bk. 4. The GH book -- bk. 5. The IJ book -- bk. 6. The KL book -- bk. 7. The MN book -- bk. 8. The OP book -- bk. 9. The QR book -- bk. 10. The STU book -- bk. 11. The VW book -- bk. 12. The XYZ book.
Title from container.
Issued in container.
Keywords: Alphabet books; Animals -- Juvenile literature; Alphabet; Animals; Alphabet; Animals